Political Interconnection in the Operation of Digital Terrestrial Free-to- Air Television Broadcasting - Rahayu Rahayu (Policy & Governance Review, 2018)
Agent(s) role in the implementation of policies is frequently considered as the determining factor for the success of policy implementation. This is reflected quite clearly in the “principle- agent” theory that describes how self-interested agent influences the implementation process. However, is self-interested agent still relevant in explaining Indonesia’s broadcasting policy implementation? What if policy implementation involved many actors with their respective personal interests? How will agents position themselves amidst numerous personal interest- bearing actors? By using the political economy approach, this research aims to reveal the role of agents in the constellation of actors’ relation to Indonesia’s broadcasting policy implementation. The operation of digital terrestrial free-to-air television broadcasting case is used to provide a reflection of agents’ position and political behavior in responding to the interest among actors. This research was conducted using the qualitative approach by implementing the data collection technique through in-depth interviews and document analysis. The research result shows that broadcasting policy implementation is not merely influenced by a self-interested agent but is also influenced by political interconnection and multiple-principles’ political-economic interest.